Remote Sensing-Based Mapping of Soil Health Descriptors Across Cyprus - Varvaris, Ioannis; Pittaki-Chrysodonta, Zampela; Themistokleous, George; Koumoulidis, Dimitrios; Ouerfelli, Dhouha; Eliades, Marinos; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2025)
Accurate and spatially detailed soil information is essential for supporting sustainable land use planning, particularly in data-scarce regions such as Cyprus, where soil degradation risks are intensified by land fragmentation, water scarcity, and climate change pressure. This study aimed to generate national-scale predictive maps of key soil health descriptors by integrating satellite-based indicators with a recently released geo-referenced soil dataset. A machine learning model was applied to estimate a suite of soil properties, including organic carbon, pH, texture fractions, macronutrients, and electrical conductivity. The resulting maps reflect spatial patterns consistent with previous studies focused on Cyprus and provide high resolution insights into degradation processes, such as organic carbon loss, and salinization risk. These outputs provide added value for identifying priority zones for soil conservation and evidence-based land management planning. While predictive uncertainty is greater in areas lacking ground reference data, particularly in the northeastern part of the island, the modeling framework demonstrates strong potential for a national-scale soil health assessment. The outcomes are directly relevant to ongoing soil policy developments, including the forthcoming Soil Monitoring Law, and provide spatial prediction models and indicator maps that support the assessment and mitigation of soil degradation.
Keywords: soil health descriptors; machine learning; Soil Monitoring Law; remote sensing; soil degradation; soil health risk assessment; SOC; soil prediction models